Nadroparin Plus Compression Stockings versus Nadroparin Alone for Prevention of Venous Thromboembolism in Cerebellopontine Angle Tumour Excisions: A Cohort Study - Koopmans, Raoul J.; Cannegieter, Suzanne C.; Koot, Radboud W.; Vleggeert-Lankamp, Carmen L. A. (Thrombosis and Haemostasis, 2020)
Background Both compression stockings and low molecular weight heparin (LMWH) are used for the prevention of post-operative venous thromboembolism (VTE) in cerebellopontine angle (CPA) tumour excisions.Objective In an attempt to optimise the prophylactic treatment in these patients, we compared LMWH (nadroparin) plus compression stockings to nadroparin as single therapy.Methods Patients undergoing CPA tumour excision in the period between January 2014 and November 2015 received nadroparin as a single therapy. Patients treated since November 2015 received, in addition to this therapy, peri-operative compression stockings as VTE prophylaxis due to a change in protocol. VTE was defined as symptomatic deep vein thrombosis or pulmonary embolism and was confirmed via radiological imaging or autopsy.Results A total of 146 consecutive patients were reviewed. Treatment groups were comparable with respect to demographics and risk factors. Six of the 60 patients (10.0%; 95% confidence interval [CI] 3.8–20.5) receiving nadroparin single therapy developed symptomatic VTE. One out of 86 patients (1.2%; 95% CI 0–6.3) treated with combination therapy developed VTE (p = 0.019) with a risk difference of 8.8% (95% CI 1.43–19.0). In comparison to combination therapy, nadroparin single therapy showed a relative risk of 8.6 (95% CI 1.1–69.6).Conclusion Adding compression stockings to peri-operative nadroparin, as a prophylactic strategy for thromboembolic complications in patients undergoing surgical intervention for CPA tumours, was associated with a significant reduction in the occurrence of VTE.
Keywords: venous thromboembolism; cerebellopontine angle; low molecular weight heparin; nadroparin; compression stockings